Improving Public and Environmental Health Through Clean and Healthy Living Behavior Education and Bacterial Examination - Prayekti, Endah; Santoso, Andreas Putro Ragil; Sunaryo, Merry; Indaryanti, Reski Novita; Rahmawati, Lili Susan; Kamelia, Dina (Indonesia Berdaya, 2026)
A major problem frequently faced by the public is clean and healthy living behaviors (PHBS). According to the Indonesian Ministry of Health in 2014, health can be achieved by changing unhealthy behaviors into healthy ones and creating a health-supportive environment. Effective measures include handwashing with soap and environmental inspections. This activity aims to increase public awareness of the importance of clean and healthy living behavior (PHBS), while also introducing the dangers of microbiological contamination that can occur on hands and water. Community service activities are carried out through the stages of pre-test, education, post-test, sampling, and sample examination. Of the 34 respondents, the majority experienced a significant reduction in hand bacteria, with 21 showing a reduction in hand bacteria of more than 70% and some reaching 99–100%. Well water examinations at several public facilities for Pekingan village residents showed the presence of Coliform bacteria exceeding the safe limits according to the Ministry of Health Regulation, indicating that the water is not suitable for direct consumption due to possible contamination by domestic waste, septic tank seepage, or poor environmental sanitation. The conclusion of this Community Service activity is that there is an increase in respondents' understanding and an increase in their ability to practice proper handwashing. Water sanitation in public facilities needs to be considered and improved because it should not be used for consumption.